Enhancing Insect Diversity in Agricultural Grasslands: The Roles of Management and Landscape Structure - Di Giulio, Manuela; Edwards, Peter J.; Meister, Erhard (The Journal of applied ecology, 2001)
1. During the last few years a variety of methods have been applied in Switzerland to preserve and enhance biological diversity in agricultural systems. The purpose of this study was to evaluate grassland management techniques in respect of their effectiveness within a managed area and to examine how these areas contribute to species diversity at a landscape scale. 2. We examined insect diversity in grasslands subject to different management in a heterogeneous landscape in part of the Swiss Jura. Four study areas with varying landscape structure were selected and, in each area, meadows of two grassland management types were investigated. 3. The true bugs (Heteroptera) were chosen as an indicator group for insect diversity on the basis of previous work that had shown that the richness of the bug fauna correlates strongly with total insect diversity. 4. The variance of the heteropteran species data was partitioned into spatial (area) and management components. Area accounted for 35.4%, management for 29.7% and the interaction management × area for 7.2% of the species variance. The species diversity was greater in extensively managed meadows than in intensive ones; extensive sites had more individuals and showed a more even rank abundance distribution. 5. Individual species differed in their responses to management. Two species benefited from intensification whereas six species were affected negatively by intensive management. Two main groups of species did not appear to respond to management; these were mostly widespread species occurring in a variety of habitats, and polyphagous species which live in a wide range of grasslands but which show a certain affinity to managed meadows. 6. Our study indicates that extensive management of grasslands can enhance both local and regional insect diversity in agricultural landscapes. Extensively managed meadows were species-rich habitats that supported some rare and specialized species. In contrast, the bug community of intensive meadows was dominated by more widespread and less specialist species.